(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Asthma is a common chronic disease in developing countries. The main objective of the study was to provide insights into adherence and asthma control predictors in two federal teaching hospitals in Nigeria, using validated instruments. For the data analysis, the level of statistical significance was set as p < 0.05. Seventy-eight patients with asthma provided consent for study participation. Every time domestic fuel was utilized at home, asthma control decreased by 1.246 units, p = 0.029. Every time an asthma patient utilized one of the hospitals which did not have a separate Asthma Clinic, adherence decreased by 1.483 units, p < 0.001. The study reveals the need for patients with asthma to minimize the use of domestic fuel. Renewable energy sources could be considered. A separate Asthma Clinic can provide ample time for asthma reviews. Dhaka Univ. J. Pharm. Sci. 21(1): 45-51, 2022 (June)